Valuing nature’s contributions to people: the IPBES approach - Pascual, U; Balvanera, P; Díaz, S; Pataki, G; Roth, E; Stenseke, M; Watson, R; Başak Dessane, E; Islar, M; Kelemen, E; Maris, V; Quaas, M; et al. (Elsevier, 2017)
Nature is perceived and valued in starkly different and often conflicting ways. This paper presents the rationale for the inclusive valuation of nature's contributions to people (NCP) in decision making, as well as broad methodological steps for doing so. While developed within the context of the Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES), this approach is more widely applicable to initiatives at the knowledge–policy interface, which require a pluralistic approach to recognizing the diversity of values. We argue that transformative practices aiming at sustainable futures would benefit from embracing such diversity, which require recognizing and addressing power relationships across stakeholder groups that hold different values on human nature-relations and NCP.